TEACHER'S SOCIAL SUPPORT AS A PREDICTOR MOTIVATION OF STUDENT ACHIEVEMENTS - Yenssy Marvilen Fanggidae, Markus Dimu Radja (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The aim that will be achieved in this research is to investigate the influence of teachers' social support to the motivation of the achievement of class XI students the language department in SMA Negeri 5 Kupang City. The research method used is quantitative, with a simple linear regression data analysis technique. The number of respondents involved in this study was as much as 35 students, and the sampling techniques used were random sampling. The results showed that the teacher's social support contributed positively and significantly to the motivation of the achievement of class XI students the language department in SMA Negeri 5 Kupang City (Sig. 0.000 < 0.05). While the contributions of effective teachers' social support variables the teachers to the motivation of achievement of 58.8%, and the remaining 41.2% are influenced by other variables that are not included in this research model. The results of this research proved that the increasing teachers' social support, the increase also the motivation of achievement of students.